Are perceptions of community safety associated with respiratory illness among a low-income, minority adult population? - Kristen N. Arthur; Rhonda Spencer-Hwang; Synnøve F. Knutsen; David Shavlik; Samuel Soret; Susanne Montgomery (BMC, 2018)
Abstract Background Growing evidence suggests social disadvantage magnifies the harmful health effects of environmental hazards; however, there is limited research related to perceptions of risk among individuals who live near such environmental hazard sites. We explored the association between individual-level perception of community safety and respiratory illness among low-income, minority adults who live in a region with routine poor air quality exacerbated by the emissions of a nearby freight railyard. Methods Interview-administered household surveys were collected (87% response rate; n = 965) in English/Spanish from varying distances surrounding a freight railyard (analytic total n = 792: nearest region n = 215, middle n = 289, farthest n = 288). Illness outcome was an affirmative response to doctor-diagnosed asthma, bronchial condition, emphysema, COPD, or prescribed-inhaler usage. Respiratory symptoms outcome was an affirmative response to chronic cough, chronic mucus, or wheezing. The independent variable was perceived community safety. Results Outcome prevalences were similar across environmental hazard regions; 205 (25.9%) were diagnosed-illness cases and 166 (21.0%) diagnosis-free participants reported symptoms. Nearly half (47.5%) of participants reported lack of perceived community safety, which was associated with environmental hazard region (p <  0.0001). In multivariable log-binomial regression models adjusting for covariables (age, gender, race/ethnicity, smoking status, smoke exposure, residential duration, and distance from the railyard) respiratory illness diagnosis was associated with lack of perceived community safety (PR = 1.39; 95% CI 1.09, 1.76). Sensitivity analyses showed a non-significant but increasing trend in the strength of association between safety perceptions and illness diagnoses with closer proximity to the railyard. Conclusions Our findings contribute to the literature that individuals' perceptions of community safety are associated with adverse respiratory health among a population living in high air pollution exposure areas.